2023
DOI: 10.1371/journal.pone.0281884
|View full text |Cite
|
Sign up to set email alerts
|

Living with “long COVID”: A systematic review and meta-synthesis of qualitative evidence

Abstract: Objectives Long-term health consequences of coronavirus disease (COVID-19), also known as “long COVID,” has become a global health concern. In this systematic review, we aimed to synthesize the qualitative evidence on lived experiences of people living with long COVID that may inform health policymaking and practice. Methods We searched six major databases and additional sources and systematically retrieved relevant qualitative studies and conducted a meta-synthesis of key findings using the Joanna Briggs In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 56 publications
0
28
1
1
Order By: Relevance
“…As documented in recent literature reviews, a growing body of qualitative research shows that living with persistent symptoms following COVID-19 infection may lead to extensive changes in people's everyday lives, health, socio-economic circumstances and identity, but knowledge of how these elements may evolve remains limited [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As documented in recent literature reviews, a growing body of qualitative research shows that living with persistent symptoms following COVID-19 infection may lead to extensive changes in people's everyday lives, health, socio-economic circumstances and identity, but knowledge of how these elements may evolve remains limited [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Missel et al [8] found that being afflicted by COVID-19 virus did not only affect the biology of the body but was also experienced as a threat to ordinary existence, bodily perceptions and usual social relationships. On their way towards a new normality, people furthermore have described the body as marked and how it made them feel vulnerable and isolated in their social life [5][6][7]9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies in Germany and UK assessing ongoing post-COVID symptoms or illness severity rather than self-perceived recovery directly have also found protective effects against ongoing symptoms for those with higher educational qualification levels [16], higher income [17], and those employed and economically active [11]. A UK qualitative study also identified a slow recovery process and socio-economic challenges to recovery as themes for individuals living with long COVID [18].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative Studien zeigen, dass sich die verschiedenen Symptome, die die Betroffenen erleben, gegenseitig verstärken können und als Symptomkomplex zu erheblichen Einschränkungen des Alltags und des Arbeitslebens führen. Psychosozial wird dies als sehr belastend beschrieben [12].…”
unclassified